Toward a postproblematic history: Rethinking the discipline in the wake of the linguistic turn - Pihlainen, Kalle (Sociedade Brasileria de Teoria e Historia de Historiografia, 2026)
The article advances the idea of a "postproblematic" history, arguing that the discipline move beyond its persistent focus on epistemology and the attendant fact-fiction debate. It sees these discussions as at an impasse and hindering the field's development. A postproblematic approach entails two key shifts. First, it rejects the seemingly unresolvable epistemological debate that has dominated discussions. Second, it asks that historians abandon the search for "answers." Instead, it urges them to embrace their roles as both antiquarians and politically engaged actors, collecting and presenting historical information while acknowledging that the meanings imposed on the past are inextricably tied to present-day concerns and values. This overall shift requires revisiting earlier theoretical positions, including a reconsideration of the ethical implications of poststructuralist thought, a rethinking of the societal role of the historian, and reaching a better appreciation of the ethical relationship between historian and reader.